Republican Legal Theory - Sellers, M. author. aut Link
X, 200 p.
Keywords: Republican legal theory developed out of the jurisprudential and constitutional legacy of the Roman res publica as interpreted over two millennia in Europe and North America. In this book - the most comprehensive study of republican legal ideas to date - Professor Sellers traces the development of republican legal theory. Explaining the importance of popular sovereignty, the rule of law, the separation of powers and other essential republican legal characteristics, he argues that these republican institutions have introduced a new era of justice into politics.